Improvement Risk Level Pada Proyek Gas Insulated Substation Sawangan Menggunakan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) - Syahabuddin, Agus; Sudiman, Sudiman (Jurnal Optimalisasi, 2024)
The implementation of construction projects always has the potential for danger or risk that can cause considerable losses regarding costs, materials, and time. Every workplace always has the risk of work accidents that can disrupt work activities in a project. The factors that cause work accidents are the lack of understanding of good Occupational Safety and Health (K3) and also the lack of implementation of the Occupational Health and Safety Management System (SMK3) in the project. The work on the Sawangan Gas Insulated Substation project is one of the projects with a fairly high level of risk in the construction world. This study aims to identify K3 risks, assess risks, and determine their control in order to reduce the level of risk. The method used in risk assessment in this study is Hazard Identification Risk Assessment and Risk Control (HIRARC). The stages used are identifying hazards, assessing risks and determining the controls used to compile K3 goals and targets to be achieved. Based on the results of this study, the Risk Rating can be reduced from 575 Risk Rating to 401 Risk Rating. After the risk control process was carried out, there was an increase, namely: High risk decreased by 65.6% from 32 to 11, Moderate risk decreased by 9.5% from 21 to 19, and for Low risk it increased from 0 to 23. The highest risks were found in commissioning and test function work, installation brickwall and roofing for control building, and tower foundation excavation.